Back Cover: Plasmonic locator with sub‐diffraction‐limited resolution for continuously accurate positioning. Issue 2 (24th April 2022) - Gao, Peng Fei; Zou, Hong Yan; Gao, Ming Xuan; Li, Yuan Fang; Huang, Cheng Zhi
Abstract : The accurate positioning at the nanoscale is important for the analysis of micro/nano interactions. Herein, a plasmonic locator is presented which consists of a heterotypic pair of red/blue plasmonic components. Attributed to the detuned energy (∼0.64 eV), the plasmonic locator has the ability of sub‐diffraction‐limited resolution (center to center, 30 nm) and accurate positioning under conventional dark‐field microscopy. (Aggregate. 2022;3:e167 ).